Improvement in yield and fruit quality of mango (Mangifera indica) with organic amendments - RAM, R A; SINGHA, ATUL; SINGH, VINOD KUMAR (The Indian Journal of Agricultural Sciences, 2019)
A field experiment was laid out to observe response of various organic amendments on soil, plant nutrient status, soil microbial properties, yields and fruit quality parameters of mango (Mangifera indica L.) cv. Mallika. Application of biodynamic compost (30 kg/tree), cow pat pit (100 g), BD- 500 and BD- 501 as soil and foliar spray for two years (2015-16) improved the soil organic carbon (1.20%) at 0-15 cm and (1.19%) at 15-30 cm soil depth, available N (168.93 ppm), P (27.67 ppm), Zn (3.78 ppm), Cu (14.78 ppm) and Mn (2.54 ppm) at 0-15 cm and organic carbon (0.98%), available N (151.20 ppm), K (200.85 ppm), Cu (9.46 ppm) and Mn (2.13 ppm) at 15-30 cm soil depth.Leaf N (2.35%), Zn (39 ppm), Cu (41.00 ppm), Mn (72.67 ppm) and Fe (256.0 ppm), total soil bacterial population (69.17 × 108) at 0-15 cm and (23.57 × 108) at 15-30 cm soil depth, actinomycetes (60.91 × 106) at 0-15 cm depth and (38.94 × 106) at 15-30 cm soil depth were also improved.Dehydrogenase activity, fluorescein diacetate activity, alkaline and acid phosphatase activity, in 0-15 cm and 15-30 cm soil depth were 4.57 and 4.09 μg TPF/g soil/h; 944.33 and 798 mg fluorescein/g/h; 136.37 and 86.56 μg PNP/g/hr and 70.01 and 80.26 μg PNP /g/h, respectively. Improvement in the yield (134.64 kg/tree), total soluble solids contents in fruit (24.93 0Brix), total carotenoids content (5.95 mg/100g), FRAP (60.03 micromole/liters) and DPPH (anti-oxidant) per cent inhibition (71.90%) was also recorded.